Swine conjunctivitis outbreaks associated with Mycoplasma hyorhinis. (September 2019) - Resende, Talita P.; Pieters, Maria; Vannucci, Fabio A.
Conjunctivitis is an uncommon finding in commercial swine herds, and the etiology of the disease is rarely studied. We investigated cases of conjunctivitis in 3 wean-to-finish swine farms. Eye swabs and tissues were obtained from clinically affected pigs (8–22 wk of age), from unaffected pigs in contact with affected pen-mates, and from age-matched pigs from an unaffected herd. Real-time PCR (rtPCR) testing for Mycoplasma hyorhinis demonstrated consistent detection and high bacterial load in samples from affected herds (clinically affected animals and non-clinical pen-mates). Ct values in affected pigs were 18.9–25.3; values were 36.4–38.6 in unaffected pigs from unaffected herds. Additionally, M. hyorhinis was identified within inflamed palpebral conjunctivae by in situ hybridization. The association of rtPCR and in situ detection of M. hyorhinis, along with the lack of detection of other potential pathogens and noninfectious causes, suggests the involvement of M. hyorhinis in the etiology and pathogenesis of the reported swine conjunctivitis.